Media Massa: Dalam Jerat Jaring Neoliberalisme - Narendra, Pitra (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
Neoliberalism has allowed the increasingly globalization of mass media flourishing within the control of a few multinational corporation. Privatization of the mass media held by the neoliberals has been presented as evident for the sceptics that mass media fail to perform as the fourth estate in democratic society. Ownership of the media by private capital would destroy the media independence.